2012
DOI: 10.1089/aid.2010.0371
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of HIV Early Infant Diagnosis and HIV Type 1 RNA Viral Load Determination on Dried Blood Spots in Cameroon: Challenges and Propositions

Abstract: The testing of dried blood spots (DBSs) for human immunodeficiency type 1 (HIV-1) proviral DNA by PCR is a technology that has proven to be particularly valuable in diagnosing exposed infants. We implemented this technology for HIV-1 early infant diagnosis (EID) and HIV-1 RNA viral load determination in infants born of HIV-1-seropositive mothers from remote areas in Cameroon. The samples were collected between December 2007 and September 2010. Fourteen thousand seven hundred and sixty-three (14,763) DBS sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…DBS samples are regularly used for early infant diagnosis and generally accepted as a sensitive method when venous blood cannot be collected [1], [39][41]. Although all studies reviewed here showed good sensitivity, the specificity was slightly less than with fresh blood samples (99–100%).…”
Section: Discussionmentioning
confidence: 83%
“…DBS samples are regularly used for early infant diagnosis and generally accepted as a sensitive method when venous blood cannot be collected [1], [39][41]. Although all studies reviewed here showed good sensitivity, the specificity was slightly less than with fresh blood samples (99–100%).…”
Section: Discussionmentioning
confidence: 83%
“…Rates of specimen rejection vary considerably and there is a paucity of data describing the frequency of each specimen quality issue. 15,16 Data such as specimen quality should be analysed in order to review the performance of HIV-1 PCR testing in the field and to standardise DBS specimen collection methods, storage and testing. 14 This study has shown that analysing specimen quality can identify health facilities which require targeted interventions, such as retraining of healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…HIV testing of children less than 18 months was done using DNA/RNA PCR. The PCR was done at the Centre Pasteur du Cameroun in the framework of the ANRS Pediacam study (27) and at the Chantal Biya International Research Center (CBIRC) (28). The children were referred to the CME-FCB either for diagnosis of HIV in those suspected to be infected or for further management of the already diagnosed HIV infection.…”
Section: Study Frameworkmentioning
confidence: 99%